Green innovation adoption in automotive supply chain: the Malaysian case - Zailani, S.; Govindan, K.; Iranmanesh, M.; Shaharudin, M.R.; Chong, Y.S. (Elsevier, 2015)
Green innovation has currently been receiving a great deal of international attention because of the growing concern of consumers, governments, and the community as a whole with regard to the degradation of natural resources and environmental pollution. The automotive sector is one of the leading generators of industrial waste that affect the quality of the natural environment. This study aims to investigate the determinants of green innovation adoption and its effect on firm performance. Data were gathered by surveying 153 firms in the Malaysian automotive supply chain industry. Data were analyzed using the partial least squares technique. Environmental regulations, market demand, and firm internal initiatives have a positive effect on green innovation initiatives (GII), while GIIs have a positive effect on the three categories of sustainable performance (i.e., environmental, social, and economic). These results have important implications for designing strategic plans for the Malaysian automotive industry. (C) 2015 Elsevier Ltd. All rights reserved.